Conservation in Museums and Inclusion of the Non-Professional. Issue 1 (6th June 2014) - Saunders, Jill
Just as object meanings are defined by people, so too can identities of individuals, groups and communities be implicit in their relationships with particular objects. The transformative quality of the museum environment and display formats, with regard to objects and object relationships, is fundamental to the socio-cultural responsibilities of these institutions and their ability to affect social issues. To understand the potential utility of heritage conservation in this respect, it is necessary to explore the complexity of the relationships that can form between objects and people and so establish some key issues and implications of conservation activities. This paper first addresses the role of materiality and material interactions in the construction and communication of identity aspects, and considers professional conservation with regard to these relationships. It will be shown that material interactions can have great significance concerning identity and that the subjectivity of object values is a key issue in the conservation of material heritage. It will be seen that though the management of heritage can be problematic, the resonance of heritage status gives museums a unique capacity for addressing both intangible and tangible social needs.